Wear characteristics of Al-Al2O3 composites produced by powder metallurgy process - Srivastava M.K.; Mandal R.K.; Mohan S.; Pathak J.P.; Ojha S.N. (My University, 2025)
Wear characteristics of Al-base composites containing 5 to 20 vol % Al2O3 have been investigated and compared with those of commercial purity aluminium used a matrix phase and a commercial 7010 grade Al-alloy. All the materials have been synthesized by powder metallurgy method using hot compaction and hot extrusion processes and wear testing has been carried out in dry sliding condition using a pin-on-disc type machine. The wear rate of composites is observed to be lower than that of the aluminium compacts but higher than the commercial grade alloy. An increase Al2O3 led to decrease in wear rate of composites, under the applied load of 5 to 35 N and sliding velocity from 0.25 to 1.5 ms-1. The possible reasons for this behaviour are discussed in light of the microstructure of the alloy and nature of the worn surfaces of the specimens.